Electromyography and Anticoagulation. Issue 5 (21st March 2013) - Gertken, J.T.; Patel, Atul T.; Boon, Andrea J.
Abstract: Needle electromyography (EMG) is a common and safe diagnostic procedure. Although there are no absolute contraindications to performing an EMG, medically induced coagulopathy represents a relative contraindication. The purpose of this article is to discuss EMG safety for patients taking anticoagulants and antiplatelet agents, and to review the current literature regarding bleeding risks. Safety measures used to avoid serious bleeding complications are also discussed.